Petrology of the Creignish Hills Pluton, Cape Breton Island, Nova Scotia - White, Chris; Barr, Sandra; Campbell, R. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
Mapping and petrologic studies of the Creignish Hills Pluton in the Bras d'Or Terrane of central Cape Breton Island have shown that the pluton consists mainly of tonalite-diorite and coarse-grained monzogranite units, with smaller areas of granodiorite-tonalite, granodiorite-monzogranite, and fine-grained monzogranite. Petrographic and chemical characteristics of the tonalite-diorite suggest that hornblende fractionation (± biotite accumulation) may have produced much of the observed variation in the unit, whereas feldspar fractionation was the dominant process producing variation within each of the other units. The tonalite-diorite unit is interpreted to be late Precambrian (ca. 560 Ma) in age like most other dioritic and tonalitic plutons in the Bras d'Or Terrane. It is probably not co-genetic with the intermediate and felsic units of the pluton. The latter may be of Early Ordovician age (ca. 495 Ma) on the basis of penological similarities of the coarse-gTained monzogranite unit to the Cape Smoky and Kellys Mountain monzogranites. Like other Bras d'Or Terrane plutons, the Creignish Hills Pluton probably formed in a continental margin volcanic arc setting during and after late Precambrian to Early Cambrian subduction.